New Threats to Academic Freedom - Minerva, Francesca (Bioethics, 2014)
Using a specific case as an example, the article argues that the Internet allows dissemination of academic ideas to the general public in ways that can sometimes pose a threat to academic freedom. Since academic freedom is a fundamental element of academia and since it benefits society at large, it is important to safeguard it. Among measures that can be taken in order to achieve this goal, the publication of anonymous research seems to be a good option.